The Effect of Implementing Project-Based Learning (PjBL) on Improving English Pronunciation Skills of Class VII Students of SMPN 1 Krembung - Akbar Wiguna; Hyan Siswanto; Layyin Af’idah; Meralda Dwi Utari; Bilqista Dwi Maharani (P3I UMSurabaya, 2024)
This study evaluates the effectiveness of the Project-Based Learning (PBL) method in improving students' English pronunciation skills. The research subjects were grade VII students at SMPN 1 Kembung, who often face challenges in pronunciation, especially in the elements of stress, rhythm, pause, and intonation. Data was collected through pre-tests and post-tests as well as observation. The results of the analysis showed a significant improvement in the students' average pronunciation score, from 63.72 in the pre-test to 73.13 in the post-test, with a significant difference (t = -9.323, p < 0.001) and high correlation ( r = 0.856, p < 0.001). In addition to technical improvement, PjBL also helps increase students' speaking confidence. These findings suggest that PjBL is effective in overcoming pronunciation difficulties, and is recommended as a method that can be applied in English language learning to improve communication skills.